2014
DOI: 10.1183/09031936.00114214
|View full text |Cite
|
Sign up to set email alerts
|

Smoking adversely affects treatment response, outcome and relapse in tuberculosis

Abstract: The impact of smoking on tuberculosis outcome was evaluated in a territory-wide treatment programme.16 345 consecutive patients undergoing chemotherapy for active tuberculosis in government chest clinics in Hong Kong from 2001 to 2003 were followed up prospectively for 2 years for treatment outcome and subsequently tracked through the territory-wide tuberculosis notification registry for relapse until the end of 2012.Smoking was associated with more extensive lung disease, lung cavitation and positive sputum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
149
3
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(164 citation statements)
references
References 24 publications
7
149
3
5
Order By: Relevance
“…The mortality rate during treatment was not different between smokers and nonsmokers, in contrast to the study by LEUNG et al [14].…”
contrasting
confidence: 87%
See 1 more Smart Citation
“…The mortality rate during treatment was not different between smokers and nonsmokers, in contrast to the study by LEUNG et al [14].…”
contrasting
confidence: 87%
“…The first study, by LEUNG et al [14], conducted in a large population of tuberculosis patients observed in Hong Kong, China, between 2001 and 2003, and followed for 10 years, confirmed that smokers with tuberculosis had a more severe clinical and radiological presentation, more frequent sputum positivity at presentation and after 2 months of treatment, a lower rate of success and, if successfully cured, a higher risk of relapse. Surprisingly, these findings were observed in spite of the fact that smokers were offered brief advice for smoking cessation, and referral for further nonpharmacological and pharmacological intervention if needed.…”
mentioning
confidence: 95%
“…11,12 Some patients have characteristics that put them at risk of acquiring TB. 1,8 Some factors recognized as risk factors for TB are smoking [19][20] , presence of any immunosuppression status (use of immunosuppressive drugs, cancer or HIV infection) 10,[21][22][23][24][25][26][27] , younger or older age 28,29 , migrant status [30][31][32] , inmate status 31,33 , homelessness or institutionalization 31,34,35 , close contact with TB-infected patients 36,37 , drug use 38 , alcoholism 39 , malnutrition 40 , diabetes [41][42] and other chronic comorbidities [43][44][45] . Obesity 46 and female gender 47 seem to reduce the risk of acquiring TB.…”
Section: Introductionmentioning
confidence: 99%
“…They usually present with more advanced lesions [63] and more often suffer from www.pneumonologia.viamedica.pl the disease recurrence [64]. Cigarette smokers are also a at greater risk of death from tuberculosis [65].…”
Section: The Role Of Cigarettes Smokingmentioning
confidence: 99%